2016
DOI: 10.1038/srep29582
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 ameliorates the neurocontrol of blood pressure in the high fructose-drinking rats

Abstract: Fibroblast growth factor-21 (FGF21) is closely related to various metabolic and cardiovascular disorders. However, the direct targets and mechanisms linking FGF21 to blood pressure control and hypertension are still elusive. Here we demonstrated a novel regulatory function of FGF21 in the baroreflex afferent pathway (the nucleus tractus solitarii, NTS; nodose ganglion, NG). As the critical co-receptor of FGF21, β-klotho (klb) significantly expressed on the NTS and NG. Furthermore, we evaluated the beneficial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…It is well documented that the blood pressure is lower in females than that in age‐matched males . This notion is consistent with the recent observations reported in rodent models, indicating that females have a much higher parasympathetic activity than males and neuroprotective action of estrogen . Our previous observation has shown that, in adult female rats, there is a female‐specific subpopulation of myelinated Ah‐type baroreceptor neurons (BRNs) in nodose and baroreceptive neurons in tractus nucleus of solitary (NTS), with which an important neuroanatomical structure supports for a critical parasympathetic activity in baroreflex afferent function in females.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is well documented that the blood pressure is lower in females than that in age‐matched males . This notion is consistent with the recent observations reported in rodent models, indicating that females have a much higher parasympathetic activity than males and neuroprotective action of estrogen . Our previous observation has shown that, in adult female rats, there is a female‐specific subpopulation of myelinated Ah‐type baroreceptor neurons (BRNs) in nodose and baroreceptive neurons in tractus nucleus of solitary (NTS), with which an important neuroanatomical structure supports for a critical parasympathetic activity in baroreflex afferent function in females.…”
Section: Introductionsupporting
confidence: 90%
“…It has been widely accepted that the parasympathetic nerve activity plays a leading role against sympathoexcitation in the neurocontrol of circulation and stabilization of blood pressure . Despite the close association of the baroreflex function with parasympathetic activation and having the extensive studies on baroreflex at both afferent and efferent pathways, the underlying mechanism at cellular and physiological level is still largely unknown due to the difficulties in handling these tissues for proper physiological measurements. Over the years, we have developed a highly reliable approaches for electrophysiological recording using vagus‐nodose slice, which allows us demonstrating a critical female‐specific Ah‐type neurons in the nodose and their potential role in neurocontrol of blood pressure …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, FGF21 was found to travel across the blood-brain barrier and act centrally to regulate various functions including glucose metabolism, circadian behavior, and energy expenditure through its actions on the hypothalamus (Liang et al, 2014;Owen et al, 2014), and chronic intraperitoneal infusion of recombinant FGF21 protein exerts beneficial effects on systolic blood pressure and baroreflex sensitivity, which was associated with activation of the Akt-eNOS-NO signaling pathway on nucleus tractus solitarius and nodose ganglion in high-fructose-drinking rats (He et al, 2016). In addition, FGF21 was found to directly act on the hypothalamic neurons and activates the hypothalamic-pituitary-adrenal axis to release corticosterone (Liang et al, 2014), which has been widely reported to be involved in the suppression of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical studies indicated that circulating FGF21 concentrations were significantly increased and associated with blood pressure in patients with hypertension (Semba et al, 2013;Zhang et al, 2015). Interestingly, therapeutic administration of FGF21 significantly ameliorates blood pressure in the high-fructose-drinking rats (He et al, 2016). Although the metabolic functions of FGF21 are well characterized, little is known about its pathophysiological roles in hypertension, and the molecular mechanism whereby FGF21 protects against hypertension remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations are needed to understand the mechanism underlying the link between FGF19 and active vitamin D3. FGF21 was reported to reduce the BP in a rat model of hypertension (31,32). In our study, the sBP of the patients with CCBs was higher than the patients without CCBs due to insufficient BP control.…”
Section: Discussionmentioning
confidence: 46%